2023
DOI: 10.1038/s41423-023-00998-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of mesenchymal stem cells/dental stem cells and their therapeutic applications

Abstract: Mesenchymal stem/stromal cells (MSCs) are widely distributed in the body and play essential roles in tissue regeneration and homeostasis. MSCs can be isolated from discarded tissues, expanded in vitro and used as therapeutics for autoimmune diseases and other chronic disorders. MSCs promote tissue regeneration and homeostasis by primarily acting on immune cells. At least six different types of MSCs have been isolated from postnatal dental tissues and have remarkable immunomodulatory properties. Dental stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 141 publications
0
23
0
Order By: Relevance
“…Dental tissue stem cells (DTSCs) are post-natal cells; they are a significant source of mesenchymal stem cells (MSCs) that can be easily obtained through minimally invasive procedures and have been utilized in treating various diseases [15]. DTSCs exhibit high proliferation rates, the ability to differentiate into multiple lineages, and the expression of embryonic markers of MSCs such as OCT4, NANOG, SOX2, and KLF4 [4].…”
Section: Dental Tissue Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental tissue stem cells (DTSCs) are post-natal cells; they are a significant source of mesenchymal stem cells (MSCs) that can be easily obtained through minimally invasive procedures and have been utilized in treating various diseases [15]. DTSCs exhibit high proliferation rates, the ability to differentiate into multiple lineages, and the expression of embryonic markers of MSCs such as OCT4, NANOG, SOX2, and KLF4 [4].…”
Section: Dental Tissue Stem Cellsmentioning
confidence: 99%
“…DTSCs exhibit immunosuppressive activity that helps maintain homeostasis in dental tissues [15], preventing inflammatory responses. Therefore, researchers have sought molecules to improve the regenerative process of DPSCs in LPS-induced inflammation.…”
Section: Effect Of Bacterial Lps On the Biological Characteristics Of...mentioning
confidence: 99%
“…MSCs exert immunomodulatory and immunosuppressive effects through various mechanisms. They interact with immune cells such as T cells, B cells, and natural killer cells, modulating immune responses [ 43 , 44 ]. The immunomodulatory properties are attributed to the production of metabolites, cytokines, and growth factors by MSCs.…”
Section: The Impact Of Donor Sex On Msc Heterogeneity and Potencymentioning
confidence: 99%
“…The immunomodulatory properties are attributed to the production of metabolites, cytokines, and growth factors by MSCs. The immune suppressive potential of MSCs involves cell-to-cell contact and the secretion of immune regulatory molecules [ 44 46 ].…”
Section: The Impact Of Donor Sex On Msc Heterogeneity and Potencymentioning
confidence: 99%
“…There are many kinds of stem cells in the jaw. Studies have reported that the types of stem cells in the oral and maxillofacial regions include periodontal ligament stem cells (PDLSCs) originating from the periodontal ligament, dental pulp mesenchymal stem cells (DPSCs) obtained from dental pulp tissue, and jaw mesenchymal stem cells (JBMSCs) in the jawbone ( TATULLO et al, 2015 ; TOMOKIYO et al, 2019 ; LI P. et al, 2023 ). Compared with stem cells derived from long bones, jaw stem cells exhibit a higher rate of proliferation and greater osteogenic potential ( JEYARAMAN et al, 2023 ).…”
Section: Introduction Of Stem Cells In the Jawmentioning
confidence: 99%